Train the computational thinking skill using problem-based learning worksheet for undergraduate physics student in computational physics courses. (April 2020) - Muliyati, D; Tanmalaka, A S; Ambarwulan, D; Kirana, D; Permana, H
Abstract: Thinking steps of computational thinking skills have an essential role in forming creative thinking to find ideas in a structured manner. Not only developing creative thinking, but this stage also helps understand how to implement ideas into computational procedures. This study aims to design worksheets for helping the students understand and improve Computational Thinking Skill (CTS) in the material interpolation with the problem based learning (PBL) strategy. The development of worksheets using step: define, design, development, and disseminate. The development stage includes the evaluation from learning expert. In many studies, the application of PBL shows an increase in various student abilities. This research applied to 39 students of computational physics courses. The result shows there was an increase in CTS, such as abstraction from the complex problem, algorithm automation, data analysis, collection, and representation.